Irisan Profile of Obese Women After Moderate Intensity Aerobic Exercise - Naufal Firdaus; Sugiharto Sugiharto; Desiana Merawati (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Irisin in obesity was found to be lower than in individuals with normal weight. Low irisin levels lead to decreased metabolism. Low metabolism causes a decrease in muscle mass, storage of triglyceride energy, and accumulation of excess fatty acids in the body which can lead to the risk of obesity. This study aims to prove the effect of moderate-intensity aerobic exercise on increasing irisin levels in obese women. This research method is true experimental with a random calculation design between pretest-posttest groups. A total of 18 obese women aged 20-25 years were actively involved in research activities and were divided into two groups, namely KK (n = 9; control group), and KE (n = 9; experimental group). Aerobic exercise was given using a set intensity of 60-70% HRmax with a treadmill for 45 minutes, 3x/week for 8 weeks. Irisin levels were evaluated before and after the intervention using the ELISA Kit method. The data analysis technique used the Paired Sample T-Test with a 5% confidence level. The results showed the average irisin level between before and after the intervention in KK (0.83±0.97 vs. 0.86±1.25 ng/mL, p=0.961), KE (0.69±0.64 vs. 2.77±1.26 ng/mL, p=0.003). Based on the results of the study it was concluded that aerobic exercise with a set intensity of 60-70% HRmax performed 3x/week for 8 weeks can increase irisin levels in obese women.